SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMILIHAN JENIS INVESTASI DENGAN METODE FUZZY MULTI CRITERIA DECISION MAKING - Susy Rosyida (Jurnal Sistem Informasi, 2014)
Abstract— The development of these days, the day everything is growing. One of these investments, the investment is a very important asset for the benefit of the future. In addition it can make land investment promising business. Investment objective to obtain a fixed income in each period. There are several kinds of investments, such as savings in the bank, deposits, gold, property and others. In investing need to know the correct matching of assets to invest in accordance with the wishes and needs. One method that can be used in the design of a decision support system that is using fuzzy multi-criteria decision making (MCDM). Based on the research conducted by aggregating the weights of criteria and the degree of suitability of each alternative with the criteria resulting interval value under the provisions of interval values. And can know the type of investment most highest total value of the integral is the type of investment property as an asset that can be selected.